Opportunities and Challenges in Improving Patient Safety - Dewi Puspa Rianda; Novian Aldo (PT. Anagata Sembagi Education, 2026)
Patient safety is a fundamental aspect of the healthcare system that plays a crucial role in ensuring the quality and standards of care. This article aims to analyze the opportunities and challenges in efforts to improve patient safety through a literature review approach. The method used is a literature review, examining various relevant scientific sources related to patient safety, including national and international journals, reports from health organizations, and other academic publications. The results of the review indicate that patient safety is influenced by various factors, including system-related aspects, human resources, technology, and organizational culture. Opportunities for improving patient safety can be identified through the utilization of digital technology, the implementation of evidence-based practice, the strengthening of a safety culture, and the active involvement of patients and their families. However, there are still a number of challenges to be addressed, such as resource constraints, the complexity of the healthcare system, an unsupportive organizational culture, and low public health literacy. Therefore, a holistic and integrated approach involving various stakeholders is needed to create a safe, effective, and sustainable healthcare system.